Jean de Saintré | Barnegidslet (Vol. 14):To franske ridderfortællinger - Antoine de La Sale (Romanske Skrifter, 2006)
The two translated stories date from the 15th century and deal with chivalry and chivalrous ideals in the late Middle Ages. The first story is a novel which describes an example of courteous love that ends up with the infidelity of the beloved lady, the punishment of the rival, a young abbot, and the unmasking of the lady. This novel gives a vivid picture of life at the royal French court and the splendour and luxury displayed at the numerous jousts in which the hero is a constant winner. The story, which is the first original French prose novel, is characterized by a pleasant tone, vivid dialogues and a realistic description of the settings. The second story is a harrowing account of the execution of an infant hostage during the Hundred Years' War. The French commandant of the fortress of Brest refuses to surrender this town to the besieging English, hereby sacrificing his only son whom he has delivered as a hostage. He makes this cruel choice, strongly urged by his wife, in order to save his chivalrous honour. The story is part of a longer text which is intended to bring consolation to a distinguished noblewoman, who is encouraged to follow the example of the mother of the sacrificed child by summoning all her strength of mind and submitting to the will of God.